THE PREVALENCE OF MASKED HYPERTENSION AMONG OLDER PATIENTS WITH COGNITIVE COMPLAINTS. (June 2018) - De Heus, R.; Peters, E.; Claassen, J.
Abstract : Objective: Although the clinical relevance of masked hypertension ([MHT] defined as normal office BP, but elevated BP at home) is still debated, it has been associated with sustained hypertension and higher cardiovascular morbidity, both established risk factors for cognitive decline. Data about MHT in elderly with cognitive problems is scarce. Therefore, the aim of this study was to estimate the prevalence of MHT in older patients visiting a memory clinic and to examine the association between MHT and cognitive function. Design and method: We studied 249 patients who attended our memory clinic. They were subjected to 7-day home BP measurements (Microlife WatchBP Home), twice in the morning and evening. Patients were included if they had at least 8 measurements left, after discarding measurements of day 1, and if office BP (single, supine) was available. The following definitions were applied: MHT (office BP < 140/90 mmHg; home BP >=135/85 mmHg), normotension (office BP < 140/90 mmHg; home BP < 135/85 mmHg), hypertension (office BP >= 140/90 mmHg; home BP > =135/85 mmHg), white-coat hypertension (office BP > =140/90 mmHg; home BP < 135/85 mmHg). Characteristics of the group with MHT were compared to those with normotension. Statistical analyses were performed using independent samples t-test, Mann-Whitney U-test and chi-square test, using P < 0.05. Results: From 202 patients (73.3 ± 9.3 years, 52% male) office and home BP was available. Office BP and home BP significantly differed (157/84 ± 23/10 mmHg and 139/79 ± 16/9 mmHg, respectively, P < 0.0001). The prevalence (with 95% CI) of MHT was 6.9% (3.4–10.4), corresponding to 14 patients. Normotension was observed in 12.4% (n=25), hypertension in 55.0% (n = 111) and white-coat hypertension in 25.7% (n = 52). Characteristics of patients with MHT and normotension are shown in Table 1. We observed a trend (P = 0.08) for a lower cognitive score on the CAMCOG test battery in MHT compared to normotension. Conclusions: Our findings show a lower prevalence of MHT compared to earlier studies performed in older people. Based on results from this relatively small group, patients with MHT may show decreased cognitive function compared to patients with normotension. However, further studies with larger numbers are needed to confirm this. Figure. No caption available.